2016
DOI: 10.1104/pp.15.01216
|View full text |Cite
|
Sign up to set email alerts
|

The tae-miR408-Mediated Control of TaTOC1 Genes Transcription Is Required for the Regulation of Heading Time in Wheat

Abstract: ORCID IDs: 0000-0002-1560-7935 (J.Y.W.); 0000-0002-3129-5206 (X.S.Z.).Timing of flowering is not only an interesting topic in developmental biology, but it also plays a significant role in agriculture for its effects on the maturation time of seed. The hexaploid wheat (Triticum aestivum) is one of the most important crop species whose flowering time, i.e. heading time, greatly influences yield. However, it remains unclear whether and how microRNAs regulate heading time in it. In our current study, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 97 publications
1
57
0
1
Order By: Relevance
“…These proteins have been described containing a copper atom, and participate in redox processes [96], with a crucial role in the electron shuttle in plants [97]. In addition, Yao et al [98] described the blue copper protein genes as the targets of miR408 in wheat, which is involved in the regulation of gene transcription required for heading time [99]. In our study SNP620 was also found in proximity to a gene coding for an ubiquinone biosynthesis O-methyltransferase.…”
Section: Discussionsupporting
confidence: 60%
“…These proteins have been described containing a copper atom, and participate in redox processes [96], with a crucial role in the electron shuttle in plants [97]. In addition, Yao et al [98] described the blue copper protein genes as the targets of miR408 in wheat, which is involved in the regulation of gene transcription required for heading time [99]. In our study SNP620 was also found in proximity to a gene coding for an ubiquinone biosynthesis O-methyltransferase.…”
Section: Discussionsupporting
confidence: 60%
“…To investigate the expression patterns of wheat ZIM ‐ like genes ( TaZIM‐A1 , TaZIM‐A2 and TaZIM‐A3 ), under different photoperiodic conditions, we performed quantitative reverse‐transcription PCR (qRT‐PCR) analysis, using TIMING OF CAB1 ( TaTOC‐A1 ), a typical circadian rhythm‐regulated gene in wheat, as a control (Zhao et al ). As expected, a very clear circadian rhythm was observed for TaTOC‐A1 expression under LD, SD, constant light (LL) and constant dark (DD) conditions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA of TOC1 starts to accumulate at the beginning and reaching its maximum level at the end of the light period, where it directly represses the transcription of the myeloblastosis (MYB) transcription factors LATE ELONGATED HYPOCOTYL ( LHY ) and CCA1 . In wheat, Zhao et al (2016) recently demonstrated that the microRNA tae-miR408 targets and down-regulates expression levels of all three wheat paralogs of TaTOC1 (TaTOC-A1 , TaTOC-B1 , and TaTOC-D1) under both LDs and SDs, thereby regulating heading time and associated agronomic traits.…”
Section: Flowering Time In Cereal Crops: a Complex Interplay Between mentioning
confidence: 99%